PHYSIOLOGICAL AND ANATOMICAL RESPONSES OF COMMON BEAN (PHASEOLUS VULGARIS L.) TO NICKLE NANOPARTICLES FOLIAR SPRAY - Sirwa . A. Qadir; C. N. Fathulla (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Nickel is an essential nutrient for plant growth with low concentrations, its excessive amounts in soil above threshold values could be cause in toxicity. The main objectives of the present research were to determine the effects of nickel nanoparticles foliar spray with 20, 40 and 70 nm diameter on the physiological characters and anatomical aspects of Phaseolus vulgaris L. plants. Lowest reduction significantly (P < 0.01) in root and shoot biomass was recorded due to in 70 nm; the measurements 0.08 and 0.05 g per plant and highest root: shoot; 0.65 as compared with control treatment. As well as the lowest conserved water content; 40% was observed in size 70 nm. While in size 40 nm Nickle nanoparticles increased chlorophyll a, b, total and carotenoids pigment contents. When the nickel nanoparticles size increased, the shoot and root tissue Ni concentrations also increased. However, the rate of Ni in root was greater than that observed in the shoot. While the Mn, Fe, Cu and Zn levels decreased due to applying nickel nanoparticles. The size of nanoparticles effects on the anatomical characteristics or structures such as stem, and leaf, also effects on the size of stomata.